2018
DOI: 10.2196/10439
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Knowledge Translation Resource for Families and Service Providers (The “F-Words” in Childhood Disability Knowledge Hub): Developmental and Pilot Evaluation Study

Abstract: BackgroundThe “F-words in Childhood Disability” (Function, Family, Fitness, Fun, Friends, and Future) are an adaptation and an attempt to operationalize the World Health Organization’s (2001) International Classification of Functioning, Disability and Health (ICF) framework. Since the paper was published (November 2011), the “F-words” have attracted global attention (>12,000 downloads, January 2018). Internationally, people have adopted the “F-words” ideas, and many families and service providers have expresse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…In 2014, an integrated research team, including parents and researchers, formed at CanChild to disseminate and study the uptake of the F‐words proactively. To date, the research team has published two papers on their dissemination work (Cross et al, ; Cross et al, ). The additional four sources in this category described the F‐words research team's work as an example of stakeholder‐driven and knowledge translation research (Longo, Galvão, Ferreira, Lindquist, & Shikako‐Thomas, ; Phoenix et al, ; Rosenbaum, ; Miller & Rosenbaum, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, an integrated research team, including parents and researchers, formed at CanChild to disseminate and study the uptake of the F‐words proactively. To date, the research team has published two papers on their dissemination work (Cross et al, ; Cross et al, ). The additional four sources in this category described the F‐words research team's work as an example of stakeholder‐driven and knowledge translation research (Longo, Galvão, Ferreira, Lindquist, & Shikako‐Thomas, ; Phoenix et al, ; Rosenbaum, ; Miller & Rosenbaum, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the publication of the F‐words paper in 2012, there has been increasing national and international interest and uptake by people around the world. In 2014, an integrated research team of parents and health services researchers was formed to promote and study systematically the dissemination and implementation of the F‐words in practice (Cross et al, ; Cross, Rosenbaum, Grahovac, Kay, & Gorter, ). Since then, the research team has worked with many stakeholders (including families, service providers, and administrators) to develop and share tools and resources to support the adoption of the F‐words in practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown that such resources are often poorly explored and evaluated [29, 30]. Recent work by Cross et al involved participation between families and researchers in the area of childhood disability to develop, implement and evaluate a web-based KT resource to promote adoption of the ‘F-words’ concepts [15]. The project used the Knowledge-To-Action Framework [31] to guide this process and culminated in developing a theory-informed resource that was deemed relevant and meaningful to its target audiences.…”
Section: Discussionmentioning
confidence: 99%
“…KT efforts have predominantly focused on increasing awareness and understanding among targeted populations regarding specific clinical topics, disease areas and potential treatments, rather than explaining methodological aspects of healthcare research that are relevant to the general public, such as the importance of evidence synthesis [12-14]. In addition, there is a distinct lack of evidence regarding the development of existing KT resources and how to incorporate an evidence-based approach, and a limited number of examples exist describing this process [15].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies were considered of poor quality due to small sample size (Barnfather et al, 2011;Burgstahler & Crawford, 2007;Cole et al, 2017;Gwynette et al, 2017;Jiam, Hoon Jr, Hostetter, & Khare, 2017;Stewart et al, 2011), convenience sampling strategy (Burgstahler & Crawford, 2007;Cross et al, 2018;Gwynette et al, 2017;Jiam, Hoon, Hostetter, & Khare, 2017;Margalit & Raskind, 2009;Stewart et al, 2011), and no description of validation of the assessment tool (Burgstahler & Crawford, 2007;Cole et al, 2017). The risk of bias was assessed using the six domains of the Cochrane collaboration's tool for assessing risk of bias (Higgins & Altman, 2008).…”
Section: Quality Of Studies and Risk Of Bias Assessmentmentioning
confidence: 99%